BASE pleasures: the behavioural, artisanal, social and emotional dimensions of academic writing - Sword, Helen; Sorrenson, Peter; Ballard, Madeleine (Studies in higher education, 2020)
This article explores the affordances, limitations and future potential of the Writing BASE, a heuristic tool designed to help academic writers identify their strengths and weaknesses in four foundational areas of their writing practice: behavioural, artisanal, social and emotional. After describing the development of the tool, we report on two separate but related studies based on the BASE rubric: (1) a statistical analysis of questionnaires completed by 500 advanced academic writers and (2) a content analysis of 90 recent or classic academic writing guides. The findings from these two studies shed new light on the under-valued and frequently occluded role of positive emotions in the writing process.